Effect of Amidated Low-Methoxyl Pectin on Physicochemical Characteristics of Jumbo Squid (Dosidicus gigas) Mantle Muscle Gels - Juan C. Ramirez-Suarez; Andrés Álvarez-Armenta; Guillermina García-Sánchez; Ramón Pacheco-Aguilar; Susana M. Scheuren-Acevedo; Miguel A. Mazorra-Manzano; Agustín Rascón-Chu (Food Technology and Biotechnology, 2017)
Jumbo squid (Dosidicus gigas) muscle proteins show low functionality with limited use in gel products. This work aims to assess the influence of adding the natural and commercially available fibre, amidated low-methoxyl pectin (at 0.5, 1.0, 1.5, 2.0 and 3.0 %), on the physicochemical and functional characteristics of jumbo squid (Dosidicus gigas) mantle muscle gels. The addition of 0.5 % fibre showed an immediate effect on the gel texture profile analysis, improving hardness (p<0.05) from (3.4±0.7) N of the control (no added fibre) to (5.2±0.9) N, and increasing elasticity (p≥0.05). Shear force was significant only at 3.0 % fibre addition. Water holding capacity also improved (p<0.05) with fibre addition (from 75 % in the control to 90–95 % aft er the treatments). Whiteness was affected (p<0.05) when 3.0 % fibre was added. Differential scanning calorimetry showed two endothermic transition peaks in the gels. The second peak (actin) increased (p<0.05) by 1–2 °C with fibre addition. Therefore, the present study demonstrates that amidated low-methoxyl pectin (0.5–3.0 %) is an excellent ingredient to improve jumbo squid mantle muscle protein functionality, increasing the gel texture and water retention characteristics.